Environmental Factors as a Cause of Differences in the Feet of Ecuadorian Children and Its Relation to Their Footwear - Laura Martin-Casado; Christian Barquín; Alberto Aldana-Caballero; Felix Marcos-Tejedor; Xavier Aguado (MDPI AG, 2021)
The objective of this study was to analyze the differences in foot measurements of Ecuadorian children according to their geographical location of residence, taking into account climatic differences (1). A total of 1662 children (2) participated in the study. Three groups were established: coast, mountains and amazonia. The type of footwear (3) used was recorded and the lengths, widths, perimeters, heights and angles of both (4) feet were analyzed with a 3D foot digitizer (5). The variable 'fitting of the foot to footwear' was also obtained. Children living in coastal areas presented greater lengths, widths, perimeters and heights compared to those living in the mountain (p > 0.001) and amazonia (p < 0.001) between ages 5 to 13. Mountain residents showed a greater first toe angle than coast residents (p > 0.001) aged 8 to 17. Children used shoes smaller than required by their foot length (p < 0.01). Ecuadorian children from the coast presented longer and wider feet with higher foot arches, whilst those from mountains presented greater first toe angle. The studied sample used footwear up to one size smaller than the size corresponding to their foot length. The fitting and type of footwear used according to climatic differences could be interfering with normal foot development.